Exploring the Anticonvulsant Potential of Cannabaceae Family: A Focus on GABAergic Modulation and Epilepsy Treatment - Sowmya, P. Reena; Ch. Ramya, Ch. Ramya; Anju, Anju; G. Mariappan, G. Mariappan; Pethe, Anil; Ingle, Rahul (Journal of Neonatal Surgery, 2025)
This review explored the anticonvulsant potential of various species from the Cannabaceae family, including Cannabis sativa, Humulus lupulus, Celtis integrifolia, Celtis tournefortii, and Trema orientalis. Epilepsy is a complex neurological condition influenced by multiple factors such as genetics, structural abnormalities, infections, metabolic disturbances, and immune system dysfunctions. Phytochemicals like cannabidiol (CBD) and tetrahydrocannabinol (THC) from Cannabis sativa, along with other bioactive compounds from Humulus lupulus, have shown significant anticonvulsant effects by regulating GABAergic neurotransmission. Additionally, Celtis integrifolia and Celtis tournefortii have demonstrated potential in mitigating oxidative stress, a key factor in the onset of seizures. While these findings from preclinical studies are promising, the lack of extensive clinical trials limits their immediate application in treating epilepsy in humans. This review highlighted the necessity for further research focused on isolating active compounds, studying their pharmacokinetics, and conducting clinical trials to validate their potential as effective treatments for epilepsy.